Huoxue-Jiangtang decoction ameliorates type 2 diabetes in high-fat diet and streptozotocin-induced rats - Lee, Maosheng; Tan, Yanyan; Li, Huilin; Liu, Deliang; Zhao, Hengxia (Frontiers in Pharmacology, 2025)
IntroductionA traditional Chinese herbal decoction, Huoxue-Jiangtang decoction (HXJT), has been clinically prescribed to patients with type 2 diabetes mellitus (T2DM) to improve hyperglycemia and hyperlipidemia for many years. However, the potential mechanisms underlying its anti-diabetic effects remain unclear.MethodsThe aim of this study was to explore the anti-diabetic effects and underlying molecular mechanisms of HXJT in T2DM rats, which were fed with a high-fat diet (HFD) and subsequently induced with streptozotocin (STZ). HPLC-MS analysis was performed to characterize the chemical composition of HXJT and serve as a quality control measure. The T2DM rats were treated with metformin or HXJT for 8 weeks.Results and discussionTreatment with HXJT significantly reduced hyperglycemia and improved insulin resistance in T2DM rats, as revealed by multiple assessments, including fasting blood glucose (FBG), glucose tolerance, fasting insulin levels, homeostasis model assessment of insulin resistance, insulin sensitivity index analysis, and histological examination of pancreas islets. HXJT treatment decreased blood lipid profile, including total cholesterol, low-density lipoprotein cholesterol, and triglycerides, although it did not change the rats’ body weight. The Western blot results indicated that HXJT reversed the downregulation of AKT and PI3K and markedly increased glucose transporter type 4 (GLUT4) in skeletal muscles. Moreover, the levels of glycogen synthetase (GS), hexokinase, superoxide dismutase (SOD), glycogen, and muscle glycogen in the HXJT group significantly increased relative to those in untreated T2DM group, while TNF-α levels decreased observably. In conclusion, HXJT improves insulin resistance, enhances insulin sensitivity, and helps preserve glucose homeostasis. The potential molecular mechanisms are related to the activation of PI3K/AKT and GLUT4 in skeletal muscles, either directly or indirectly.